The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1017/s0033822200033725
|View full text |Cite
|
Sign up to set email alerts
|

Development of Radiocarbon Dating in China Over the Past 50 Years

Abstract: ABSTRACT. On the arrival of the 50th anniversary of Radiocarbon, we review important developments in radiocarbon dating in China during the past 50 years, especially concerning 3 aspects: sample standard and preparation, accelerator mass spectrometry (AMS) facilities, and 14 C applications. Specifically, these events are marked by the establishment of the Chinese sucrose charcoal standard in China; the development of small-sample dating in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The first set of AMS radiocarbon data for Chinese archeological samples was reported in 1989 to support a discussion on the chronology of Shandingdong (Upper Cave) of the Zhoukoudian locality in Beijing (Chen et al, 1989). Several institutions began to set up AMS facilities at about the same time (Zhou and Chen, 2009). Peking University completed a dedicated tandem-based AMS facility in 1992, the Peking University accelerator mass spectroscopy (PKUAMS) laboratory with the financial support of the National Natural Science Foundation of China.…”
Section: Accelerator Mass Spectrometry (Ams) Radiocarbon Datingmentioning
confidence: 99%
“…The first set of AMS radiocarbon data for Chinese archeological samples was reported in 1989 to support a discussion on the chronology of Shandingdong (Upper Cave) of the Zhoukoudian locality in Beijing (Chen et al, 1989). Several institutions began to set up AMS facilities at about the same time (Zhou and Chen, 2009). Peking University completed a dedicated tandem-based AMS facility in 1992, the Peking University accelerator mass spectroscopy (PKUAMS) laboratory with the financial support of the National Natural Science Foundation of China.…”
Section: Accelerator Mass Spectrometry (Ams) Radiocarbon Datingmentioning
confidence: 99%
“…The Chinese Sugar Carbon (CSC), also reported as ''Chinese Sucrose Charcoal'' standard in some published papers [3][4][5][6], was introduced as the national radiocarbon standard in 1981 at the first Chinese National 14 C Conference [1,2,7]. We chose to use the name ''Chinese Sugar Carbon'' here because it was the original English translation on the labels of the standard bottles even though ''Chinese Sucrose Charcoal'' may be a better description of the material.…”
Section: Introductionmentioning
confidence: 99%
“…CSC had been widely used as a primary or secondary standard in some 30 conventional and AMS radiocarbon laboratories in China [6], and it played an important role in the radiocarbon dating for the Xia-Shang-Zhou chronology of Chinese ancient history, especially in helping to obtain high precision 14 C measurements on AMS at the beginning stage of the project [3,10,11]. However further measurements on 13 C indicated that CSC might not be homogenous, especially for mg-sized aliquots, and its radiocarbon content appeared to be more variable as well.…”
Section: Introductionmentioning
confidence: 99%
“…With development of the ionosphere physics, and requirements of theoretical research and practical application, the ionospheric model was attracting increasing attention for nearly 20 years. The model can be expressed as some ionospheric characteristics, or Curve or formula about some factors, such as the related fitting curve of critical frequency and sunspot numbers, et al Currently, the most representative is the International Reference Ionosphere (IRI) [1] , not only applied to HF prediction, but also to the ionosphere physics research. The IRI model prediction is also called the global .…”
Section: Introductionmentioning
confidence: 99%